The Influence of Organizational Citizenship Behavior (OCB), Job Satisfaction and Affective Commitment on Employee Turnover Intention at PT. Gudang Garam Tbk Bengkulu Branch - Renty Dwi Putri; Tezar Arianto (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of Organizational Citizenship Behavior, Job Satisfaction and Affective Commitment on the Turnover Intention of Employees of PT. Gudang Garam Tbk Bengkulu Branch. The object of this research is the employees of PT. Gudang Garam Tbk Bengkulu Branch. With a sample of 60 people. The analysis technique used is multiple linear regression test, multiple termination coefficient test, classical assumption test and t and f tests. with the data collection method using a questionnaire. The results of this study can be concluded that seen from the multiple linear regression equation using the SPSS program, namely Y = -0.900 - 0.218 (X1) - 0.189 (X2) + 0.607 (X3). The results of the analysis found that the variables Organizational Citizenship Behavior, Job Satisfaction and Affective Commitment had a positive and significant influence on turnover intention. Hypothesis testing using t-test showed that the 3 independent variables studied were proven to significantly affect the dependent variable Turnover Intention. Then through the F test, it can be seen that the variables Organizational Citizenship Behavior, Job Satisfaction and Affective Commitment have a significant effect on Turnover Intention. The R Square number of 0.830 indicates that 83% of the Turnover Intention variable can be explained by the three independent variables used. in the regression equation. While the remaining 17% is explained by other variables outside the three variables studied in this study.